Selective and simultaneous determination of NSAIDs in equine plasma by HPLC with molecularly imprinted solid-phase extraction. (August 2014) - Meucci, Valentina; Minunni, Maria; Vanni, Michele; Sgorbini, Micaela; Corazza, Michele; Intorre, Luigi
Background: Detection of nonsteroidal anti-inflammatory drugs (NSAIDs) in equine plasma is a significant analytical problem in veterinary anti-doping controls.Results: A new HPLC method coupled to selective extraction with molecularly imprinted polymers was developed for the simultaneous determination in equine plasma of the NSAIDs phenylbutazone, flunixin, oxyphenbutazone, ketoprofen and naproxen. The analytical performances of the method have been evaluated both in standard solutions and equine plasma samples.Recovery: Molecularly imprinted polymers solid-phase extraction for all NSAIDs was >94% with intra-day values below 15.0% and inter-day values below 20%. Method quantification limit was 0.01 μg/ml.Conclusion: The developed method could be considered as a useful alternative to existing screening methods for the determination of NSAIDs in the context of studies of pharmacokinetics and anti-doping controls.